牵引传动研究综述 - 陈德生; 潘荣荣 (Jixie chuandong)
Traction drives possesses some inherent advantages when compared with gears. Traction drive can be classified into two major categories:fixed ratio transmission （FRT） and continuous variable speed transmission （CVT）. Generating adequate normal load at the contact surface is essential for traction drives. There are two ways to generate the normal load between two mating surface:fixed pressure pressing and automatically pressing. As the traction capability of the traction medium available at present is not great enough,so this paper put forward an assumption of replacing the elastohydrodynamic lubricant （EHL） by the megnetorheological fluids （MRF）,in order to raise the ability of traction drive.